Budget Analysis, Employee Competence and Classification of Standard Account Charts in Realizing Reliability Financial Statements - Agus Prasetyo; Rimi Gusliana Mais (LPMP Imperium, 2021)
This research aims to analyze whether the Budget, Employee Competency and Standard Account Chart Classification (BAS) can realize the reliability of the Ministry of Maritime and Fisheries Financial Statements.This research uses descriptive research with a qualitative approach, research using interview techniques from informants. The population of this study is the Ministry of Maritime Affairs and Fisheries with the study sample determined based on work units with the authority of positions that exist within the Ministry..The results showed that dominantly employee competence can realize the reliability of the financial statements of the Ministry of Maritime Affairs and Fisheries because by placing employee competencies adjusted to the job will maximize work results. The budget and BAS can be structured properly when the competencies of employees can be met.